Analysis of jump shot performance among 14-15 year old male basketball player - Çetin, E.; Murati, S. (Procedia - Social and Behavioral Sciences, 2014)
The purpose of the study was to analyses jump shot performances of the players in different positions among 14-15 year old male basketball players. 9 basketball players (age: 14.87±0.35 year; height: 180.0±0.07 cm; weight: 70.22±11.95 kg) participated in this study. Before jump shot, the lowest and highest value of center of gravity was determined in guard (0.81 cm) and forwards (0.99 cm) players, respectively. The lowest value of knee angle and the highest value of ball release angle was determined in center players (?knee: 119.93°, aball: 39.33°). Total jump shot performance duration was record 0.51 sn in center players, 0.46 sn in guard players and 0.38 sn in striker players.